The polyvalence of fear - Ofela Palermo; Duarte, H. (9th International Research Meeting in Business and Management (IRMBAM-2018), 2018)
Our paper explores the role of fear as a to-hand resource that individuals use to respond to situations of ‘controlled’ sensebreaking-sensegiving dynamics, in a way that enables them to maintain and strengthen their social identity. Drawing on an in-depth qualitative case study, this article suggests an emergent process of identity work, one that draws upon to-hand discursive resources. The construction and maintenance of social identity in the face of external threats is thus a sustained process, in which discourses are developed and obtain, as it were, a life of their own. Our research draws on the outcomes of an ethnographic study in a regional branch of the National Probation Service in the UK that was undergoing organisational change. Our findings illustrate the sensebreaking-sensegiving dynamic cycle and reveal the unexplored creative territory that lies at the heart of social identity control and construction. Our contribution is twofold: (1) emotions are not merely an individual’s internal state but they can be the product of an ongoing ‘conversation’ with the external contexts, (2) social identity control is ambivalent (e.g. difficult to separate roles of controllers and controlled) due to the overlapping, interconnected and spontaneous identity aspects at its base